PERANCANGAN SISTEM MONITORING KELEMBAPAN TANAH PADA TANAMAN CABAI BERBASIS INTERNET OF THINGS - Rajagukguk, David; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2025)
Chili plants require proper and consistent irrigation to ensure healthy growth and optimal crop yields. However, in many agricultural settings, especially in small to medium-scale farming, the absence of a real-time monitoring system often leads to under-watering or over-watering. These issues can result in wilting, root damage, or even crop failure. To address this challenge, this study presents the development of a soil moisture monitoring system based on the Internet of Things (IoT). The system integrates a soil moisture sensor (YL-69), NodeMCU ESP8266 microcontroller, and the Blynk mobile application. The NodeMCU acts as the main controller that receives data from the sensor, processes it, and transmits the information to the Blynk platform via Wifi.The Blynk app provides a user-friendly interface that displays soil moisture conditions in real-time. Moisture levels are categorized into three conditions: dry (<50%), normal (50–70%), and wet (>70%). A Gauge widget shows the moisture percentage visually in analog form, while the SuperChart logs the historical moisture data. When moisture falls below 50%, the system triggers a notification alert to the user. The test results demonstrate accurate sensor readings, real-time data transmission, and effective notification delivery. Overall, this system enhances irrigation decision-making and helps farmers maintain optimal soil moisture, thereby improving the sustainability and productivity of chili cultivation.